2015
DOI: 10.5603/fhc.a2016.0012
|View full text |Cite
|
Sign up to set email alerts
|

Myenteric plexuses atrophy in the vicinity of colorectal cancer tissue is not caused by apoptosis or necrosis

Abstract: Introduction. The previously performed studies showed that the presence of colorectal cancer (CRC) tumor is associated with the atrophy of myenteric plexuses in the vicinity of cancer invasion; however, the possible mechanisms of this phenomenon are not known. The aim of the present study was to determine whether the atrophic changes of the enteric nervous system (ENS) within an intestine wall of the CRC patients were caused by apoptosis or necrosis and whether they were associated with changes in the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 16 publications
4
19
2
Order By: Relevance
“…They found significant reduction (by approximately 50%) of the area occupied by galanin-immunoreactive neurons in the MPs located in the vicinity of CRC invasion in comparison to distally located plexuses. The authors suggested that neither apoptosis nor necrosis has been involved in the observed phenomena [15,16]. These finding have been confirmed by the results of our ultrastructural study, which showed neither neurons' apoptosis nor necrosis to occur in myenteric plexuses located close to the CRC tumor.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…They found significant reduction (by approximately 50%) of the area occupied by galanin-immunoreactive neurons in the MPs located in the vicinity of CRC invasion in comparison to distally located plexuses. The authors suggested that neither apoptosis nor necrosis has been involved in the observed phenomena [15,16]. These finding have been confirmed by the results of our ultrastructural study, which showed neither neurons' apoptosis nor necrosis to occur in myenteric plexuses located close to the CRC tumor.…”
Section: Discussionsupporting
confidence: 80%
“…Our study presents an attempt to explain the observations by Kwiatkowski et al [15] and Kozlowska et al [16] who applied morphometry to measure the area of MPs close to and distant from CRC invasion. They found significant reduction (by approximately 50%) of the area occupied by galanin-immunoreactive neurons in the MPs located in the vicinity of CRC invasion in comparison to distally located plexuses.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Latest studies showed that ENS may undergo severe decomposition under various pathological conditions. For example, it was reported that MPs in the vicinity of the colorectal cancer (CRC) tissue were significantly smaller and had lower number of neurons per plexus compared to distally located plexuses [ 5 , 6 ]. Similar observations were also reported in the colon wall of patients with diabetes [ 7 ] and severe constipation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…These stimuli are transmitted by caspases (CASP) which can be divided into initiator (CASP8; CASP9) and executioner endoproteases (CASP3; CASP6; CASP7). Caspases can be activated via extrinsic and intrinsic pathways and both coincide at a common point, which is activation of executioner caspase that leads to protein proteolysis and DNA damage [ 5 , 11 ]. Galanin (GAL) can be another candidate which may play important role in this process.…”
Section: Introductionmentioning
confidence: 99%